Patients satisfaction with consultation at primary health care centers in Abha City, Saudi Arabia - Tabekhan, Abdullah Khlofh (J Family Med Prim Care, 2018)
AIM OF STUDY: This study aims to assess patients satisfaction regarding consultations at the General Clinics of primary health-care (PHC) centers, in Abha City. PATIENTS AND METHODS: This cross-sectional study design was conduct among adult patients attending training PHC centers in Abha City, Saudi Arabia during September 2016. The researcher designed a data collection sheet that comprised patients’ personal characteristics and the consultation satisfaction questionnaire, which contained 18 questions within four dimensions, i.e., general satisfaction; professional care; depth of relationship; and length of consultation. RESULTS: The total number of the patient included in this study was 400, more than half of them were male (54%). Most of them were Saudi (90%), married (79%), and educated (93%). More than half 53% were dissatisfied, 20% were satisfied with consultation while 27% were natural. The most important factor affecting satisfaction with consultation was age, education level and income. CONCLUSIONS: Patients satisfaction toward their consultation experience at general clinics of training PHC centers in Abha City was suboptimal. Total consultation scores differ significantly according to their age groups, education level, and monthly income. RECOMMENDATIONS: PHC physicians should be more concerned with improving medical consultations provided to their patients. Continuing medical education and training of PHC physicians about provision of medical consultation.